Gambaran Motivasi Mahasiswa Fakultas Kedokteran Gigi Universitas Andalas Berkarir Sebagai Dokter Gigi - Fildzah Nurul Fajrin; Rahmatul Aini; Reno Wiska Wulandari (Andalas Dental Journal, 2022)
Background: The motivation for selecting a dentist career is the complex consideration. Knowing and understanding dental students' motivation is important for institutions to manage learning systems to create dentists that can fulfill the needs of the community. Purpose: to describe the motives and perceptions of undergraduate and postgraduate dental students attending Faculty of Dentistry, Andalas University. This study was conducted to 120 academic and clinical students in this institution. The students were instructed to fill a questionnaire consisting of 25 questions. Eight questions were scored from 1 to 2 , 1 question was a multiple choice question and the rest were scored from 1 to 4. The data were tabulated by Microsoft Excel, factor analysis was tested by SPSS software. Results: Fifty three percent of students chose dentistry in the first place. The most common factors choosing dentistry are internal or external motivation, profession, and remuneration. Dental students showed a strong tendency to pursue higher study and managing private dental clinics. Conclusion: humanity, flexibility, and financial status were found to be important motivating factors. Hence, it may be a good idea to establish educational programs in the faculty to educate students based on their career choices.